2020
DOI: 10.1007/s00018-020-03539-2
|View full text |Cite|
|
Sign up to set email alerts
|

TP63 links chromatin remodeling and enhancer reprogramming to epidermal differentiation and squamous cell carcinoma development

Abstract: Squamous cell carcinoma (SCC) is an aggressive malignancy that can originate from various organs. TP63 is a master regulator that plays an essential role in epidermal differentiation. It is also a lineage-dependent oncogene in SCC. ΔNp63α is the prominent isoform of TP63 expressed in epidermal cells and SCC, and overexpression promotes SCC development through a variety of mechanisms. Recently, ΔNp63α was highlighted to act as an epidermal-specific pioneer factor that binds closed chromatin and enhances chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 195 publications
(244 reference statements)
0
38
0
Order By: Relevance
“…The American Cancer Society defines cancer stem celllike cells (CSCs) as a tumor cell type with self-renewal ability and multiple differentiation potential [29]; these form only a small part of tumor cells. Increasing researchers have indicated that differentiated tumor cells can regain stemness and become tumor stem cells through a process involving multiple mechanisms, including the indispensable effect of hypoxia on CSCs [30].…”
Section: Hypoxia Promotes Cancer Stem Cell Differentiation Into An Enmentioning
confidence: 99%
“…The American Cancer Society defines cancer stem celllike cells (CSCs) as a tumor cell type with self-renewal ability and multiple differentiation potential [29]; these form only a small part of tumor cells. Increasing researchers have indicated that differentiated tumor cells can regain stemness and become tumor stem cells through a process involving multiple mechanisms, including the indispensable effect of hypoxia on CSCs [30].…”
Section: Hypoxia Promotes Cancer Stem Cell Differentiation Into An Enmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC) encompasses a group of malignant tumors originating from the squamous epithelium of the oral cavity, oropharynx, larynx, and hypopharynx [96][97][98]. Puram et al…”
Section: Highlighting Intra-and Inter-tumoral Heterogeneitymentioning
confidence: 99%
“…In order to maintain the stability of the internal environment, normal cells actively and orderly trigger cell apoptosis through signal transduction mechanisms [95][96][97][98][99][100][101]. However, cancer cells can inhibit apoptosis by participating in these signaling pathways.…”
Section: N6-methyladenosine Can Influence the Apoptosisassociated Signaling Pathwaymentioning
confidence: 99%